2008
DOI: 10.1002/jpln.200700018
|View full text |Cite
|
Sign up to set email alerts
|

Do water regimes affect iron‐plaque formation and microbial communities in the rhizosphere of paddy rice?

Abstract: Pot experiments were conducted to investigate the effect of soil water regimes on the formation of iron (Fe) plaque on the root surface of rice seedlings (Oryza sativa L.) and on the microbial functional diversity in a paddy soil. The rice seedlings were subjected to three moisture regimes (submergence, 100%, and 60% water-holding capacity [WHC]), and were grown for 5 and 11 weeks. Aerobic lithotrophic Fe(II)-oxidizing (FeOB) and acetate-utilizing Fe(III)-reducing bacteria (FeRB) in the rhizosphere and non-rhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(13 citation statements)
references
References 39 publications
(34 reference statements)
2
11
0
Order By: Relevance
“…The catabolic functional diversity of microbial communities in the rhizosphere was higher than that of in bulk soil, consistent with the results in paddy rice (Chen et al ,2008), This may be due to the higher (or diversity of) carbon resources in the rhizosphere soil, which is considered as the driving force for microbial density and activity (Bowen & Rovira 1999;Lugtenberg & Dekkers 1999). A gelatinous film on the root surface, which is a primary source of nutrients and energy amongst soil microbes, has been reported in a variety of ecosystems (Salt et al, 1998).…”
Section: Discussionsupporting
confidence: 89%
“…The catabolic functional diversity of microbial communities in the rhizosphere was higher than that of in bulk soil, consistent with the results in paddy rice (Chen et al ,2008), This may be due to the higher (or diversity of) carbon resources in the rhizosphere soil, which is considered as the driving force for microbial density and activity (Bowen & Rovira 1999;Lugtenberg & Dekkers 1999). A gelatinous film on the root surface, which is a primary source of nutrients and energy amongst soil microbes, has been reported in a variety of ecosystems (Salt et al, 1998).…”
Section: Discussionsupporting
confidence: 89%
“…It should also be noted that the Fe formation on root surfaces can be influenced by many abiotic factors such as the availability of soil Fe, temperature, pH, CO 2 , soil permeability, etc. (Chen et al 1980;St-Cyr and Crowder 1988), as well as biotic factors, including ROL and rhizosphere bacteria (St-Cyr and Crowder 1989;Chen et al 2008). Mendelssohn et al (1995) reported that ROL is the most important biotic factor controlling Fe plaque formation.…”
Section: Discussionmentioning
confidence: 99%
“…Rice seedling preparation and culture conditions Rice (O. sativa L.) seeds were surface sterilized in 30 % H 2 O 2 solution for 15 min and thoroughly washed with deionized water (Chen et al 2008). The seeds were germinated in moist perlite.…”
Section: Methodsmentioning
confidence: 99%